Fiscal redistribution in comparative perspective: Recent evidence from the Luxembourg Income Study (LIS) Datacenter - David K. Jesuit; Vincent A. Mahler (Luxembourg Income Study (LIS), 2017)
This paper offers an overview of income inequality and government redistribution between the late 1960s and 2010 in 20 developed countries. Our primary data source is household-level income surveys available from the Luxembourg Income Study Database (LIS). These data allow us to measure overall redistribution; to explore whether redistribution has been achieved primarily through direct taxes or social transfers; to compare the redistributive effect of old-age pensions and transfers to those of working age; and to explore several approaches to second-order feedback effects whereby taxes and transfers affect private sector income. We find that there is substantial cross-national variation in overall fiscal redistribution and that transfers account for the majority of redistribution in the countries we examine. With respect to changes over time, we find that overall redistribution has increased steadily since the early 1970s in most countries and has largely, but not entirely, kept pace with a substantial growth of private sector inequality.
Keywords: 330